Sub-inhibitory Effects of Antimicrobial Peptides - Vasilchenko, Alexey S.; Rogozhin, Eugene A. (Frontiers in Microbiology, 2019)
Antimicrobials, and particularly antimicrobial peptides (AMPs), have been thoroughly studied due to their therapeutic potential. The research on their exact mode of action on bacterial cells, especially at under sublethal concentrations, has resulted in a better understanding of the unpredictable nature of bacterial behavior under stress conditions. In this review, we were aiming to gather the wide yet still under-investigated knowledge about various AMPs and their subinhibition effects on cellular and molecular levels. We describe how AMP action is non-linear and unpredictable, also showing that exposure to AMP can lead to antimicrobial resistance via triggering various regulatory systems. Being one of the most known types of antimicrobials, bacteriocins have dual action and can also be utilised by microorganisms as signaling molecules at naturally achievable sub-inhibitory concentrations. Unpredictable nature of AMP action and the pathogenic response triggered by them remains an area of knowledge that requires further investigation.